2021
DOI: 10.55563/clinexprheumatol/4nb0ku
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and well-being during the COVID-19 pandemic: stress vulnerability, resilience and mood disturbances in fibromyalgia and rheumatoid arthritis

Abstract: Objective. The COVID-19 pandemic severely increased the stress levels in the population. The aim of present study was to investigate the impact of the lockdown measures on emotional well-being and disease activity in patients with fibromyalgia (FM) and rheumatoid arthritis (RA) through a telemedicine approach.Methods. An on-line survey, including demographic characteristics, disease-activity and psychometric scales (Stress-related Vulnerability Scale, Resiliency scale), Zung Anxiety and Depression Self-assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
5
16
1
1
Order By: Relevance
“…Obtaining repeated data from the same people at similar periods in the year would have yielded insight into how many people deteriorated and ameliorated. However, our results are not inconsistent with most studies measuring intra-individual changes in smaller samples of people with fibromyalgia [ 10 12 ]. We did not have perfect norm data, because the norm group is from 25 years ago and included 35% men, which may have yielded somewhat lower scores in our sample of women with fibromyalgia.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…Obtaining repeated data from the same people at similar periods in the year would have yielded insight into how many people deteriorated and ameliorated. However, our results are not inconsistent with most studies measuring intra-individual changes in smaller samples of people with fibromyalgia [ 10 12 ]. We did not have perfect norm data, because the norm group is from 25 years ago and included 35% men, which may have yielded somewhat lower scores in our sample of women with fibromyalgia.…”
Section: Discussioncontrasting
confidence: 68%
“…There were earlier studies indicating that mental and physical health, such as reflected in fibromyalgia severity scores, was not worse [ 8 , 10 , 11 ] and perhaps even better [ 12 ] during than before the pandemic. Only one study observed a lower health during the pandemic [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations